Adaptive Charging System for PEM Fuel Cells Using a 4-Switch Buck-Boost Converter - Kaur, Puneet (Current Approaches in Engineering Research and Technology Vol. 9, 2024)
Proton Exchange Membrane (PEM) fuel cells are integral to clean energy applications, often necessitating the integration of batteries to ensure consistent power delivery. A critical requirement in such systems is the precise matching of the battery voltage to the PEM fuel cell's output voltage to achieve optimal performance. Additionally, since PEM fuel cells operate as current-output systems, meticulous control of current is essential to maintain the fuel cell at its peak performance point, thereby maximizing both efficiency and lifespan. This paper introduces an adaptive 4-switch buck-boost DC-DC converter specifically designed to charge batteries from PEM fuel cells while ensuring voltage compatibility and optimal current management. The converter's interleaved design effectively minimizes ripple and enhances thermal management. Furthermore, the study compares the performance of single-phase and four-phase converter configurations, demonstrating the superior efficiency and stability of the four-phase approach. Simulation results validate the converter's effectiveness, presenting a robust solution for the seamless integration of PEM fuel cells with battery systems.